Valuing Freedom and History in the Middle East: A Review of Mazinani’s ‘Full Freedom’ Model - Kalb, Zep (Politikon: The IAPSS Journal of Political Science, 2015)
This paper qualitatively compares Mazinani’s model for the measurement of freedom, the called Full Freedom model, with the Human Development Index (HDI) and the Freedom of the World Index (FWI) and examines the advantages and disadvantages of using this model for the measurement of freedom in the Middle East and North Africa (MENA). The particularity of historical trajectories in the MENA will be held against the HDI and FWI. Then, shortcomings in Mazinani’s model for the measurement of freedom will be assessed in relation to this model’s dependency on its two competitors.